Insulin Sensitivity, Depression/Anxiety, and Physical Fitness in At-Risk Adolescents - Bruggink, Stephanie M.; Shomaker, Lauren Berger; Kelly, Nichole R.; Drinkard, Bart E.; Chen, Kong Y.; Brychta, Robert J.; Cassidy, Omni; Demidowich, Andrew P.; Brady, Sheila M.; Tanofsky-Kraff, Marian; Yanovski, Jack A. (Sports Medicine International Open, 2019)
Poor physical fitness contributes to the early progression of cardiometabolic disease, yet the physiological and psychological factors underpinning poor fitness in at-risk adolescents are not well understood. In this study, we sought to determine the relationship of physical fitness with two developmental phenomena of adolescence, insulin resistance and depression/anxiety symptoms among at-risk youth. We conducted secondary data analyses of 241 overweight or obese adolescents (12–17 years), drawn from two study cohorts. Insulin sensitivity index was derived from oral glucose tolerance tests. Adolescents self-reported depressive symptoms and anxiety symptoms on validated surveys. A walk/run test was administered to determine perceived exertion and physical fitness (distance traveled). Insulin sensitivity was positively associated with walk/run distance (b=0.16, P<0.01), even after accounting for all covariates. Anxiety symptoms were inversely related to perceived exertion (b=–0.11, P<0.05), adjusting for covariates. These findings suggest that insulin resistance and anxiety symptoms are associated with different dimensions of physical fitness in overweight or obese adolescents and could both potentially contribute to declining fitness and worsening metabolic outcomes in at-risk youth.
Keywords: adolescents; physical fitness; depression; anxiety; insulin sensitivity